USP14 as a Therapeutic Target Against Neurodegeneration: A Rat Brain Perspective - Banerjee, Chayan; Roy, Moumita; Mondal, Rupsha; Chakraborty, Joy (Frontiers in Cell and Developmental Biology, 2020)
In the recent past, many of the deubiquitinases (DUB) were found to modulate mitochondrial clearance or mitophagy and thus they are currently projected as therapeutic targets against neurodegeneration. Among these DUBs, USP14 stands at a distinctive juncture, since it can influence both proteasome complex activity and autophagy process. USP14 interference can enhance mitochondrial clearance and thus can protect Parkinsonian phenotypes in Drosophila model. However, in higher animal models of neurodegenerative disorders, evaluation of the protective role of USP14 is yet to be done. In this perspective, we pointed out a few of the major considerations that should be classified before designing experiments to evaluate the therapeutic potential of this DUB in rodent models of neurodegeneration. These are mainly: level of USP14 in the concerned brain region and how the level alters in the model system. Because USP14 mediated mitophagy is Prohibitin2 dependent, the anticipated impact of this protein in this aspect is also discussed. To illustrate our view, we show that USP14 levels increases in adult rat brain substantia nigra (SN) and cerebellum compared to the young ones. We also depict that rotenone treatment can immediately lead to increased SN specific USP14 levels. Our perception thus portrays USP14 as a therapeutic target, especially for addressing SN specific neurodegeneration in adult rat brain, but may vary with the disease model.